Learning Banyuwangi Traditional Music at Sanggar Jiwa Etnik Blambangan: A Model of Inheritance and Innovation - Aris Setiawan; Zulkarnain Mistortoify; Yuddan Fijar Sugmatimur (Journal of Urban Society's Arts, 2025)
This study examines the mechanisms of traditional music transmission at Sanggar Jiwa Etnik Blambangan in Banyuwangi, a rapidly growing sanggar (studio) where most members are young learners. The research focuses on the learning process, supporting factors, and documentation strategies that can be replicated as a teaching model for curriculum development in arts institutions. Specifically, this study supports plans to establish an arts campus in Banyuwangi. The research employs a participatory ethnographic approach, structured interviews, and creative organizational analysis to explore pedagogical interactions, sanggar structure, and innovations in musical practice. The theoretical framework integrates Lave & Wenger’s community of practice, Florida’s creative organization concepts, and an ethnomusicological approach to analyze musical structures and their social contexts. Findings reveal that Sanggar Jiwa Etnik Blambangan employs effective methods to simplify complex musical patterns, incorporates cultural context in each learning session, and makes traditional music more engaging and accessible to younger generations. This process not only enhances the accessibility of traditional music education but also fosters greater interest and active participation among sanggar members. These findings reinforce the potential of the sanggar’s learning model as a reference for arts curriculum development, particularly in the context of establishing an arts campus in Banyuwangi.